Perspectives on the Third Crusade in the Novel "Malk ul Aziz Varjina" - Raj, Asia; Bibi, Tehseen; Mughal, Raees Ahmed (sourcecoder, 2024)
Abdul Halim Sharar (1860-1926) in his Urdu novel “Malk ul Aziz Varjina” dipicted events and impactas revolving aroud the Third Crusade. This short article is an effort to identify the differences and similarities in fact and fiction in the novel. This novel is in fact a creative rebuttle to Sir Walter Scott's novel on same theme, The Talisman (1825). Walter Scott presented Christian perspective that in view of Sharar need correction. This sensitivity to relegious and national identity was indeed stem from the fact that after the War of Independence in 1857, Muslims of India felt humilated and helpless. The aim of these historical novels writing was to develop sense of glory of Islam in the young generation. After comparing and analyzing the events of the third crusade in the novel with other historical books, some differences and commonalities are revealed which helped in reaching the historical authenticity; and thus, shed light on mutual boundries as well as limitations of the history and the literature.